Faktor-faktor yang berhubungan dengan penyembuhan luka post sectio caesarea - Eva Yunitasari; Feni Elda Fitri (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Background:  Post-cesarean section patients usually require hospitalization for around 3-5 days after surgery. Complications after surgery can also prolong the length of treatment and recovery in the hospital and one of the factors in the wound healing process in post-cesarean section patients can be influenced by nutrition, mobilization and personal hygiene. Purpose: To determine the factors related to the wound healing process in post-cesarean section patients at Bhayangkara Hospital Bandarlampung. Method: This type of research is quantitative with a cross-sectional design. The population in this study were post-cesarean section patients at Bhayangkara Hospital Bandarlampung, with an average of 62 mothers per month. The number of samples taken was fifty people. The chi-square test was used to test the bivariate. Results: Of the three factors that influence wound healing after CS at Bhayangkara Hospital Bandarlampung, these three factors have the greatest influence on wound healing. Nutrition has a significant correlation (p=0.018), mobility has a significant correlation (p=0.000), and personal hygiene has a significant correlation (p=0.000). Conclusion: There is a significant relationship between nutritional factors, mobilization, and personal hygiene with wound healing.   Keywords: Mobilization; Nutrition; Post Sectio Caesarea wound healing; Personal Hygiene.   Pendahuluan: Pasien post sectio caesarea biasanya membutuhkan waktu rawat inap sekitar 3-5 hari setelah operasi. Komplikasi setelah tindakan pembedahan, juga dapat memperpanjang lama perawatan dan pemulihan dirumah sakit dan salah satu faktor proses penyembuhan luka pada pasien post sectio caesarea dapat dipengaruhi oleh nutrisi, mobilisasi dan personal hygiene. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan proses penyembuhan luka pada pasien post sectio caesarea di Rumah Sakit Bhayangkara Bandarlampung. Metode: Jenis penelitian ini adalah kuantitatif dengan dengan rancangan cross sectional. Populasi dalam penelitian ini adalah pasien post Sectio Caesarea di Rumah Sakit Bhayangkara Bandarlampung terhitung dengan rata-rata perbulan 62 ibu. Jumlah sampel yang diambil adalah lima puluh orang. Uji chi square digunakan untuk menguji bivariat. Hasil: Dari tiga faktor yang mempengaruhi penyembuhan luka setelah SC di Rumah Sakit Bhayangkara Bandarlampung, ketiga faktor tersebut paling banyak mempengaruhi penyembuhan luka. Nutrisi memiliki korelasi signifikan (p=0.018), mobilitas memiliki korelasi signifikan (p=0.000), dan kebersihan pribadi memiliki korelasi signifikan (p=0.000). Simpulan: Ada hubungan yang bermakna antara faktor nutrisi, mobilisasi, dan personal hygine dengan penyembuhan luka.   Kata Kunci: Mobilisasi; Nutrisi; Penyembuhan luka Post Sectio Caesarea; Personal Hygiene.